2015
DOI: 10.1002/eat.22426
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of weight‐control behavior among 15 year old girls

Abstract: Objective The objectives were to identify and predict patterns of weight control behavior in 15 year old (yo) girls and to examine weight control group differences in energy intake. Method Subjects included 166 girls assessed every 2 years (ys) from age 5 to 15. Latent class analysis was used to identify patterns of weight control behaviors. Antecedent variables (e.g. inhibitory control at 7ys), and concurrent variables (e.g. BMI and dietary intake at 15ys) were included as predictors. Assessments were a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 54 publications
2
28
2
1
Order By: Relevance
“…Girls of mothers who reported dieting were almost three times more likely to attempt dieting by age 11. This effect was not moderated by daughters' weight status at age 5, despite previous findings that body weight promotes risk factors for eating pathology such as dieting, 16 potentially suggesting that weight may play more of a role later in childhood and adolescence. The relatively small sample may have limited the ability to detect significant interactions: only 37 girls were categorized as overweight at baseline.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Girls of mothers who reported dieting were almost three times more likely to attempt dieting by age 11. This effect was not moderated by daughters' weight status at age 5, despite previous findings that body weight promotes risk factors for eating pathology such as dieting, 16 potentially suggesting that weight may play more of a role later in childhood and adolescence. The relatively small sample may have limited the ability to detect significant interactions: only 37 girls were categorized as overweight at baseline.…”
Section: Discussioncontrasting
confidence: 69%
“…16 At baseline, participants included 197 five-year-old girls (mean age = 5.4 -0.4) and their mothers. Eligibility criteria for girls' participation at baseline included living with the biological parents, the absence of severe food allergies or chronic medical problems affecting food intake, and the absence of dietary restrictions involving animal products.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, in the HIGH group, the changes in ED pathology were not significantly correlated with reductions in weight, indicating that for children with comorbid obesity and ED pathology, large reductions in weight status are not necessary to see changes in ED pathology. The discrepancy in findings between the dieting and obesity‐treatment literatures is likely due to differences in the energy‐reduction method; while most self‐initiated dieting is often accompanied by extreme restriction, particularly of specific foods and/or food groups , supervised obesity treatment focuses on encouraging more sustainable lifestyle modifications. In addition, FBT teaches parents to model healthy eating practices, use praise and positive reinforcement for healthy behaviors rather than focusing on weight or criticizing less healthy choices, and provide support (e.g., assisting with self‐monitoring) for their child's efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Attrition was primarily due to family relocation outside of the area. Additional details on the study population can be found elsewhere (10, 11). Girls with complete data on both EAH at age 7 and binge eating at age 15 (n=158) were included in the current study; there were no differences between those included in the current study and those without complete data.…”
Section: Methodsmentioning
confidence: 99%